Poly(dopamine)-modified carbon nanotube multilayered film and its effects on macrophages. (March 2017) - Sun, Xin; Shao, Han; Xiang, Ke; Yan, Ya; Yu, Xiang; Li, Diansen; Wu, Wutian; Zhou, Libing; So, Kwok-Fai; Ren, Yi; Ramakrishna, Seeram; Li, Ang; et al.
Abstract: In this study, we presented a facile functionalization of carbon nanotubes (CNTs) via dopamine self-polymerization on the outer surface of multi-walled CNTs (MWCNTs). A CNT nanocomposite was constructed through layer-by-layer assembly of polydopamine (PDA)-functionalized MWCNTs (CNT@PDA) and poly-l -lysine (PLL). Measurements by transmission electron microscopy and X-ray photoelectron spectroscopy confirmed PDA deposition on MWCNTs, and assessments by UV–vis spectroscopy indicated the sequential deposition of PLL and CNT@PDA in a linear growth of (PLL-CNT@PDA) films. We intensively investigated the activation profile and corresponding cellular events of macrophages upon their interfacing with CNT@PDA and the (PLL-CNT@PDA) film, including cell viability, intracellular reactive oxygen species production, phagocytic capacity, inflammatory responses and gene expressions. The results suggested that PDA functionalization significantly decreased inflammatory responses of MWCNTs in vitro when compared with the widely-applied carboxylic acid functionalization (COOH). Interestingly, RNAseq transcriptome analysis revealed that, unlike the control (PLL-CNT-COOH) film, the (PLL-CNT@PDA) film exerted a minor impact on gene expressions in macrophages, affecting mainly those associated with cell cycle. Moreover, no foreign-body response was found in mice bearing (PLL-CNT@PDA) film transplantation, confirming its in vivo biocompatibility. Collectively, our proposed method of PDA functionalization and particularly fabrication of CNT@PDA multilayered nanofilms may have numerous translational applications in biomedicine. Graphical abstract: